Dielectric film, and polymer actuator member and actuator using same
The dielectric film with a dispersed phase and dense layer in silicone-based actuators addresses the lack of research on phase structure and space charge distribution, achieving enhanced displacement behavior through heterocharge accumulation and interfacial polarization.
Patent Information
- Application Number
- JP2020149610
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-07
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2040-09-07
AI Technical Summary
There is a lack of research on the displacement behavior of dielectric films using silicone as a base polymer, focusing on the phase structure and space charge distribution, which is crucial for understanding the relationship between internal structure and displacement behavior in polymer actuators.
A dielectric film with a dispersed phase of a polar group-containing organic compound in a base polymer, featuring a dense layer on one surface and an asymmetric cross-sectional structure, influenced by the interaction between material polarity, phase structure, and cross-sectional structure, utilizing cyanoethyl group-containing organic compounds and modified silicone oils to enhance displacement behavior.
The dielectric film exhibits novel displacement behavior suitable for polymer actuators, with heterocharge accumulation and interfacial polarization enhancing actuator performance, allowing for efficient deformation under electric fields.
Smart Images

Figure 0007599873000002 
Figure 0007599873000003 
Figure 0007599873000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a dielectric film, and a polymer actuator member and actuator using the same. [Background technology]
[0002] Polymer actuators using polymer materials that have characteristics such as flexibility, light weight, and easy moldability are expected to be put to practical use in the smart society. Among them, dielectric elastomer actuators that operate in air have been researched and developed as flexible, soft actuators. There have been reports of the use of acrylic, silicone, polyurethane, and other dielectric elastomer materials. In particular, silicone has a wide band gap due to the siloxane bond, and therefore has characteristics such as heat resistance, weather resistance, chemical resistance, and insulation, and is used as a high-performance material in many markets.
[0003] As the driving principle of dielectric elastomer actuators, electrostatic attraction between electrodes (Maxwell stress), ion size, asymmetry of space charge distribution, etc. have been studied. Space charge distribution measurement is one of the methods to quantitatively evaluate the amount and position of charge inside a dielectric, and is widely used in particular for research on dielectric breakdown characteristics. Although there are few studies on the driving mechanism due to space charge distribution, there are reports that the driving mechanism of PVA / DMSO, PVC / plasticizer dielectric polymer gel, and polyurethane elastomer is due to asymmetry of space charge distribution (see, for example, Non-Patent Document 1). In addition, by measuring the space charge distribution of NBR, acrylic elastomer, and silicone, it has been reported that materials suitable for actuators have non-uniformity in space charge and cause dielectric breakdown under a relatively low electric field (see Non-Patent Document 2).
[0004] In recent years, research on dielectric elastomers has focused on many applications, but few studies have focused on the basic material structure. In general, even polymer composite materials of the same chemical substance have different higher-order structures depending on the manufacturing method, and their physical values may differ significantly. It is expected that the displacement behavior under voltage also changes depending on the phase structure of the material. There are few studies on displacement behavior focusing on the relationship between phase structure and space charge distribution. There are reports on the relationship between the chemical structure and displacement behavior of polyurethane (see Non-Patent Document 3) and on the analysis of the droplet phenomenon of ionic liquid in a complex of ionic liquid and silicone (see Non-Patent Document 4). However, there has been no research on displacement behavior focusing on the phase structure and space charge of a dielectric film made of a silicone-based polymer. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] Hirai, T., et al.,Chapter12,Dielectric Gels, in Soft Actuators - Materials, Modeling, Applications, and Future Perspectives,pp.169-182,Springer (2014). [Non-Patent Document 2] Tanaka, T. and Masuya, K., Peculiar Space Charge Characteristics in Some Elastomers, Proceedings of 2008 International Symposium on Electrical Insulating Materials, September7-11,(2008) [Non-Patent Document 3] M. Watanabe, N. Wakimoto, H. Shirai, T. Hirai, Journal of Applied Physics., 94(4), 2494-2497(2003). [Non-Patent Document 4] H. Okuzaki, H. Suzuki, T. Ito, J. Phys. Chem., 113, 11378-11383 (2009). Summary of the Invention [Problem to be solved by the invention]
[0006] The inventors have already found that a member containing a cyanoethyl group-containing organic compound in an organopolysiloxane composition, which is a representative and electrically stable material for chemical crosslinking, is displaced under a direct current electric field (Patent Application No. 2019-158169). The present invention aims to further analyze the relationship between the displacement behavior and internal structure of such silicone polar material composites and to provide a novel dielectric film that can be used as a polymer actuator member. [Means for solving the problem]
[0007] In order to solve the above problems, the present inventors conducted extensive research and found that the displacement behavior of a silicone polar material composite is based on the asymmetry of the space charge distribution caused by the influence of the interaction between the material polarity, the phase structure inside the material, and the cross-sectional structure. The present invention is based on such an operating principle and includes the following embodiments.
[0008] (1) A dielectric film containing a dispersed phase of a polar group-containing organic compound in a base polymer, the dielectric film having a dense layer made of the base polymer on either surface of the dielectric film. (2) The dielectric film according to (1), wherein the base polymer comprises one or more elastomers selected from silicone, polyurethane, polyacrylonitrile, nylon, polyethylene terephthalate, polypropylene, polyethylene, polyketone, polyvinyl alcohol, polyvinyl butyral, polyvinyl acetate, polymethyl methacrylate, poly-n-butyl acrylate, cellulose and wool. (3) The dielectric film according to (1) or (2), wherein the polar group-containing organic compound is a cyanoethyl group-containing organic compound, a modified silicone oil, a phthalocyanine or an ionic liquid. (4) The dielectric film according to any one of (1) to (3), wherein the cyanoethyl group-containing organic compound is at least one selected from the group consisting of cyanoethyl saccharose, cyanoethyl pullulan, cyanoethyl cellulose, cyanoethyl hydroxyethyl cellulose, cyanoethyl hydroxypropyl cellulose, cyanoethyl amylose, cyanoethyl starch, cyanoethyl dihydroxypropyl starch, cyanoethyl glycidol pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl polyhydroxymethylene, and cyanoethyl sorbitol. (5) The dielectric film according to any one of (1) to (4), wherein the modified silicone oil is a modified silicone oil having a polysiloxane chain and a fluoroalkyl group, a carboxyl group and / or an amino group bonded to an end or a side chain of the polysiloxane chain. (6) The dielectric film according to any one of (1) to (5), which has a thickness of 50 to 500 μm and an asymmetric cross-sectional structure. (7) The dielectric film according to any one of (1) to (6), wherein the dispersed phase is spherical and has a spherical diameter of 1 to 100 μm. (8) The dielectric film according to any one of (1) to (7), wherein the thickness of the dense layer is less than 10% of the total thickness of the dielectric film. (9) The dielectric film according to any one of (1) to (8), wherein the dense layer has a thickness of 5 to 50 μm. (10) A polymer actuator member comprising an electrode layer on each side of the dielectric film according to any one of (1) to (9) above. (11) An actuator comprising the polymer actuator member according to (10) above. Effect of the Invention
[0009] According to the present invention, it is possible to provide a dielectric film having a novel internal structure that can be used as a polymer actuator member. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 shows a schematic structure of a dielectric film according to one embodiment. [Diagram 2]FIG. 2 shows an outline of the electrode part of the pulsed electrostatic acoustic nondestructive testing device (PEANUT) used to measure the space charge distribution. [Diagram 3] FIG. 3 shows a schematic diagram of the deformation measurement sample. [Figure 4] FIG. 4 shows the experimental setup for measuring the deformation. [Diagram 5] Figure 5 shows cross-sectional images of the PDMS / CR-U(T)x composites prepared using tetrahydrofuran as a solvent and the PDMS / CR-U(A)x composites prepared using acetone, taken with a laser microscope. [Figure 6] Figure 6 shows enlarged images of PDMS / CR-U(T)42.9 and PDMS / CR-U(A)42.9 taken in Figure 5. [Figure 7] Figure 7 shows the dependence of the sphere diameter and dense layer thickness of the PDMS / CR-U(T)x and PDMS / CR-U(A)x composites on the amount of CR-U added. [Figure 8] Figure 8 shows the results of infrared spectroscopy analysis by attenuated total reflectance (ATR) comparing the air and PET surfaces (Figure 8(a)) and the sea and island phases (Figure 8(b)) of PDMS / CR-U(T)42.9. [Figure 9] Figure 9 shows the change in appearance over time when CR-U and PDMS were dissolved in THF or ACT, respectively: (a) CR-U(T)50, (b) CR-U(A)50, (c) PDMS(T)21, (d) PDMS(A)21, (e) PDMS / CR-U(T)42.9, and (f) PDMS / CR-U(A)42.9. [Figure 10] FIG. 10 shows the Cole-Cole plots of various silicone compositions. [Figure 11] FIG. 11 shows the relationship between the resistance and capacitance obtained from the equivalent analysis and the CR-U content. [Figure 12] FIG. 12 shows the electric field strength dependence of the AC impedance of PDMS / CR-U(T)42.9. [Figure 13] FIG. 13 shows the results of the electric field strength dependence of the resistance and capacitance obtained from the equivalent analysis. [Figure 14]FIG. 14 shows the dependence of the displacement of PDMS / CR-U(T)x and PDMS / CR-U(A)x on the amount of added CR-U after 30 minutes at a load electric field strength of 3 kV / mm. [Figure 15] FIG. 15 shows the electric field strength dependence of the displacement of PDMS / CR-U(T)42.9(a) and PDMS / CR-U(A)42.9(b). [Figure 16] Figure 16 shows the displacement and the position of the dense layer of PDMS / CR-U(T)42.9. (a) shows the displacement when the PE film is attached to the PET side, (b) shows the displacement when the PE film is attached to the air side, and (c) shows the sequence of electric field intensity. [Figure 17] Figure 17 shows the results of space charge measurements of PDMS / CR-U(T)42.9 and PDMS / CR-U(A)42.9, where (a) the air side is the anode and (b) the air side is the cathode. [Figure 18] Figure 18 shows the dependence of the space charge distribution on the amount of CR-U added for each composite when the bias polarity was changed. In (a), the air side was the anode, and in (b), the air side was the cathode. [Figure 19] FIG. 19 shows the relationship between the heterocharge peak value and the displacement of PDMS / CR-U(T)x. [Figure 20] FIG. 20 shows a schematic diagram of the space charge distribution and deformation near the anode interface when the dense layer side is used as the anode. [Figure 21] FIG. 21 shows the dependence of the compressive modulus of PDMS / CR-U(T) on the amount of CR-U added. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] First, a schematic structure of a dielectric film in one embodiment of the present invention will be described, followed by a description of a composition that is a material for the dielectric film, a method for producing the dielectric film, and a polymer actuator that is constructed using the dielectric film.
[0012] <Dielectric film> FIG. 1 shows a schematic structure of a dielectric film in one embodiment. The dielectric film 10 shown in FIG. 1 contains a dispersed phase 14 mainly made of a polar group-containing organic compound in a base polymer 13. A dense layer 11 made of a base polymer is provided on one surface of the dielectric film 10 (the upper surface in FIG. 1). The dense layer 11 is a uniform layer (sometimes called a "skin layer") made substantially of the base polymer, and preferably has a thickness of less than 10% of the entire dielectric film. The dimensions of the dielectric film 10 are not particularly limited, but it is preferable that the film has a thickness of 50 μm or more from the viewpoint of durability for use as an actuator member. In addition, the film thickness is preferably 500 μm or less in order to easily deform. Therefore, the film thickness of the dense layer 11 is preferably about 5 to 50 μm. In FIG. 1, the lower part of the dense layer 11 has a sea-island structure 12 including a dispersed phase of a polar group-containing organic compound in a continuous phase of a base polymer. The dispersed phase is mainly composed of a polar group-containing organic compound, and its shape may be spherical (true spherical or approximately spherical), ellipsoidal (elliptical sphere), polygonal (polygonal pyramid, polygonal prism such as cuboid or rectangular prism, etc.), plate-like (flat, scale-like or thin plate-like, etc.), rod-like or rod-like, fibrous, irregular, etc., but it is preferable to form a spherical dispersed phase.
[0013] On the other hand, an interface 15 exists between the sea-island structure 12 and the dense layer 11. Based on such an asymmetric structure, when an electric field is applied to both sides of the dielectric film 10, it is considered that the leakage of charges in the sea-island structure is suppressed by the dense layer 11 made of the base polymer, and hetero-charges accumulate in the vicinity thereof. From the viewpoint of efficiently causing the accumulation of hetero-charges, it is preferable that the dispersed phase 14 is spherical and has a spherical diameter of about 1 to 100 μm. More preferably, the spherical diameter of the dispersed phase is 10 to 100 μm. In this specification, the term "hetero-charge" refers to a charge of the opposite polarity to that of an electrode that exists in the vicinity of the electrode. The base polymer and the polar group-containing organic compound will be described in detail below.
[0014] <Base polymer> The base polymer of this embodiment is not particularly limited in type as long as it is a flexible elastomer, but it is preferable to include one or more elastomers selected from, for example, silicone, polyurethane, polyvinyl chloride, polyacrylonitrile, nylon, polyethylene terephthalate, polypropylene, polyethylene, polyketone, polyvinyl alcohol, polyvinyl butyral, polyvinyl acetate, polymethyl methacrylate, poly n-butyl acrylate, cellulose, and wool. The elastomer may include additives such as plasticizers, processing aids, crosslinking agents, vulcanization accelerators, vulcanization aids, anti-aging agents, softeners, and colorants. By using these relatively soft materials, the dielectric film of this embodiment can achieve large deformation characteristics. Particularly preferable is a silicone elastomer obtained by curing the organopolysiloxane composition used in the examples described below. It is also known that polyurethane elastomers, like silicone elastomers, easily deform under a DC electric field due to asymmetric accumulation of space charges (Watanabe M, Hirai T (2004) J Appl Phys 43:1446-1448). Furthermore, it may be a gel-like polymer material in which a plasticizer is added to a low-dielectric resin such as polyvinyl chloride (PVC) to increase the relative dielectric constant (see, for example, JP 2013-192333 A).
[0015] The organopolysiloxane composition as a preferred embodiment has organopolysiloxane as the main component (base polymer), but the curing method is not particularly limited, and examples thereof include conventionally known condensation curing type, addition curing type, organic peroxide curing type, radiation curing type, etc. In particular, the addition curing type is preferred. The organopolysiloxane composition that can be suitably used in this embodiment will be described in detail below.
[0016] (1) Addition-curing organopolysiloxane composition The organopolysiloxane used as the base polymer is preferably one represented by the following average composition formula (1).
[0017] R a SiO(4-a) / 2 (1) Here, R is the same or different, substituted or unsubstituted, monovalent hydrocarbon group preferably having 1 to 12 carbon atoms, particularly 1 to 10 carbon atoms, and examples thereof include alkyl groups such as methyl, ethyl, propyl, butyl, 2-ethylbutyl, and octyl groups; cycloalkyl groups such as cyclohexyl and cyclopentyl groups; alkenyl groups such as vinyl, hexenyl, and allyl groups; aryl groups such as phenyl, tolyl, xylyl, naphthyl, and diphenyl groups; aralkyl groups such as benzyl and phenylethyl groups; or groups in which some or all of the hydrogen atoms bonded to the carbon atoms of these groups are substituted with halogen atoms, cyano groups, etc., and further groups substituted with or containing amino groups, ether groups (-O-), carbonyl groups (-CO-), carboxyl groups (-COOH), sulfonyl groups (-SO2-), etc., such as chloromethyl groups, trifluoropropyl groups, 2-cyanoethyl groups, and 3-cyanopropyl groups, with methyl groups, vinyl groups, phenyl groups, and trifluoropropyl groups being preferred, and methyl groups being particularly preferred. Of these, it is preferred that 80 mol % or more, and particularly 90 mol % or more of R are methyl groups. a is 1.90 to 2.05.
[0018] In this case, the organopolysiloxane used is an organopolysiloxane having at least two alkenyl groups, preferably vinyl groups, in one molecule. The alkenyl groups may be present either at the ends of the molecular chain or within the molecular chain.
[0019] The crosslinking agent may be an organohydrogenpolysiloxane having at least two, and particularly three or more, SiH groups in one molecule. As this organohydrogenpolysiloxane, a known one may be used, for example, an organohydrogenpolysiloxane represented by the following average composition formula (2):
[0020] R' b H c SiO (4-b-c) / 4 (2) (In the formula, R’ represents a substituted or unsubstituted monovalent hydrocarbon group having 1 to 12 carbon atoms, particularly 1 to 10 carbon atoms, similar to the above R, and those without an aliphatic unsaturated bond are preferred. b is 0 ≦ b < 3, particularly 0.7 ≦ b ≦ 2.1, c is 0 < c ≦ 3, particularly 0.002 ≦ c ≦ 1, and b + c is a positive number where 0 < b + c ≦ 3, particularly 0.8 ≦ b + c ≦ 3.) Those represented by are exemplified. The usage amount is preferably such that the SiH group is 0.3 to 10 moles, particularly 0.5 to 5 moles, per mole of the alkenyl group of the main component organopolysiloxane.
[0021] The addition reaction catalyst may be a known one, and a metal of Group VIII or a compound thereof, particularly a platinum compound, is preferably used. Examples of this platinum compound include chloroplatinic acid, complexes of platinum with olefins, etc. The addition amount of the addition reaction catalyst is 0.1 to 2000 ppm, particularly 1 to 500 ppm, as the metal of Group VIII, based on the organopolysiloxane of the base polymer.
[0022] (2) Condensation reaction type organopolysiloxane composition When the organopolysiloxane composition is a condensation-curing type, the base polymer is preferably a diorganopolysiloxane blocked at both molecular chain ends with hydroxyl groups or organooxy groups such as alkoxy groups having 1 to 4 carbon atoms.
[0023] As the crosslinking agent for this condensation-curing type organopolysiloxane composition, a silane or siloxane compound having two or more hydrolyzable groups in one molecule is preferred. In this case, examples of the above hydrolyzable groups include alkoxy groups such as methoxy group, ethoxy group, butoxy group, ketoxime groups such as dimethylketoxime group, methylethylketoxime group, acyloxy groups such as acetoxy group, alkenyloxy groups such as isopropenyloxy group, isobutenyloxy group, amino groups such as N-butylamino group, N,N-diethylamino group, amide groups such as N-methylacetamide group, etc. The compounding amount of this crosslinking agent is preferably 2 to 50 parts by mass, particularly 5 to 20 parts by mass, based on 100 parts by mass of the above both-end hydroxyl group (or organooxy group) blocked organopolysiloxane.
[0024] Condensation curing type organopolysiloxane compositions generally use a curing catalyst. Examples of the curing catalyst include alkyl tin ester compounds such as dibutyltin diacetate, dibutyltin dilaurate, and dibutyltin dioctoate, titanate esters or titanium chelate compounds such as tetraisopropoxytitanium, tetra n-butoxytitanium, tetrakis(2-ethylhexoxy)titanium, dipropoxybis(acetylacetonato)titanium, and titanium isopropoxyoctylene glycol, organometallic compounds such as zinc naphthenate, zinc stearate, zinc-2-ethyloctoate, iron-2-ethylhexoate, cobalt-2-ethylhexoate, manganese-2-ethylhexoate, cobalt naphthenate, and alkoxyaluminum compounds, 3-aminopropyltriethoxysilane, and N-β(aminoethyl)γ-aminopropyl Examples of the curing catalyst include aminoalkyl group-substituted alkoxysilanes such as trimethoxysilane, amine compounds and their salts such as hexylamine and dodecylamine phosphate, quaternary ammonium salts such as benzyltriethylammonium acetate, lower fatty acid salts of alkali metals such as potassium acetate, sodium acetate, and lithium oxalate, dialkylhydroxylamines such as dimethylhydroxylamine and diethylhydroxylamine, and silanes or siloxanes containing guanidyl groups such as tetramethylguanidylpropyltrimethoxysilane, tetramethylguanidylpropylmethyldimethoxysilane, and tetramethylguanidylpropyltris(trimethylsiloxy)silane, but these are not limited to one of them and may be used as a mixture of two or more. The amount of these curing catalysts to be blended is preferably 0 to 10 parts by mass, particularly 0.01 to 5 parts by mass, relative to 100 parts by mass of the organopolysiloxane.
[0025] (3) Other curable organopolysiloxane compositions When the organopolysiloxane composition is a silicone rubber composition cured by an organic peroxide, the organopolysiloxane used as the base polymer is preferably a gum-like one having at least two alkenyl groups, such as vinyl groups, at the molecular chain terminals and / or within the molecular chain.
[0026] As the curing catalyst, an organic peroxide is used. As examples of the organic peroxide, alkyl organic peroxides such as dicumyl peroxide and di-t-butyl peroxide, and acyl organic peroxides such as benzoyl peroxide and 2,4-dichlorobenzoyl peroxide are preferably used. The amount of the organic peroxide is preferably 0.1 to 10 parts by mass, particularly preferably 0.2 to 5 parts by mass, per 100 parts by mass of the organopolysiloxane of the base polymer.
[0027] When the organopolysiloxane composition is a radiation-curable silicone rubber composition, the organopolysiloxane used as the base polymer is one having two or more aliphatic unsaturated groups, such as vinyl groups, allyl groups, alkenyloxy groups, acrylic groups, and methacrylic groups, mercapto groups, epoxy groups, and hydrosilyl groups, at the molecular chain terminals and / or in the molecular chain.
[0028] Examples of the reaction initiator include known acetophenone, propiophenone, benzophenone, xanthol, fluorene, benzaldehyde, anthraquinone, triphenylamine, carbazole, 3-methylacetophenone, 4-methylacetophenone, 3-pentylacetophenone, 4-methoxyacetophenone, 3-bromoacetophenone, 4-allylacetophenone, p-diacetylbenzene, 3-methoxybenzophenone, 4-methylbenzophenone, 4-chlorobenzophenone, 4,4'-dimethoxybenzophenone, 4-chloro-4'-benzylbenzophenone, 3-chloroxanthol, 3,9-dichloroxanthol, 3-chloro-8-nonylxanthol, benzoin, benzoin methyl ether, benzoin butyl ether, bis(4-dimethylaminophenyl)ketone, benzyl methoxyketal, and 2-chlorothioxanthol. The amount of the compound added is preferably 0.1 to 20 parts by mass, and particularly preferably 0.5 to 10 parts by mass, per 100 parts by mass of the organopolysiloxane base polymer.
[0029] The organopolysiloxane composition of the present embodiment may contain additives such as pigments, dyes, antioxidants, antioxidants, antistatic agents, antimony oxide, and flame retardants such as chlorinated paraffin.Further examples include polyethers as thixotropy improvers, fungicides, and antibacterial agents, and adhesive assistants such as aminosilanes such as γ-aminopropyltriethoxysilane and 3-2-(aminoethylamino)propyltrimethoxysilane, and epoxysilanes such as γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0030] The organopolysiloxane composition of the present embodiment can be obtained by uniformly mixing the above-mentioned components, the filler, and the above-mentioned various additives in a dry atmosphere. The curing conditions for the organopolysiloxane composition of the present embodiment are determined by a conventional method suitable for the curing type.
[0031] Specific examples of such organopolysiloxane compositions include KE-1800T-A / B, KE-1031-A / B, KE-103, KE-1051J-A / B, KE-1012-A / B, KE-106, KE-1282-A / B, KE-1283-A / B, and the like manufactured by Shin-Etsu Chemical Co., Ltd., SILPOT184 manufactured by DuPont-Toray Specialty Materials Inc., and YSR-3022, TPR-6700, TPR-6720, TPR-6721, and the like manufactured by Toshiba Silicones Co., Ltd.
[0032] <Organic compounds containing polar groups> The polar group-containing organic compound of the present embodiment includes, but is not limited to, a cyanoethyl group-containing organic compound, modified silicone oil, phthalocyanines, various ionic liquids, etc. For example, it may be selected from various polar materials that are compatible or partially incompatible with the silicone elastomer, which is the base polymer.
[0033] (Organic compounds containing cyanoethyl groups) As a preferred embodiment, the "cyanoethyl group-containing organic compound" is not particularly limited as long as it is a compound having a cyanoethyl group in the molecule, but it is preferable to use an organic polymer or organic oligomer containing a cyanoethyl group. Since the cyanoethyl group-containing organic compound has a cyanoethyl group with high polarity in the molecule, it forms a large dipole moment when placed in an electric field and exhibits a high dielectric constant.
[0034] The cyanoethyl group-containing organic compound is preferably an organic dielectric material having a dielectric constant of 10 or more. Specific examples of the cyanoethyl group-containing polymer include cyanoethyl saccharose (cyanoethyl sucrose, dielectric constant 24), cyanoethyl pullulan (dielectric constant 18), cyanoethyl cellulose (dielectric constant 16), cyanoethyl hydroxyethyl cellulose (dielectric constant 18), cyanoethyl hydroxypropyl cellulose (dielectric constant 14), cyanoethyl amylose (dielectric constant 17), cyanoethyl starch (dielectric constant 17), cyanoethyl dihydroxypropyl starch (dielectric constant 18), cyanoethyl glycidol pullulan (dielectric constant 20), cyanoethyl polyvinyl alcohol (dielectric constant 20), cyanoethyl polyhydroxymethylene (dielectric constant 10), and cyanoethyl sorbitol (dielectric constant 40). In addition, organic dielectric materials having a dielectric constant of 10 or more other than these may be used as long as they do not go against the object of the present invention.
[0035] The cyanoethyl group-containing organic compound is preferably contained in an amount of 5 to 60 mass %, and more preferably 25 to 45 mass %, based on the total amount of the composition constituting the dielectric film of this embodiment. When the content of the cyanoethyl group-containing organic compound is 5 mass % or more, the effect of improving the displacement of the actuator is high, and when it is 60 mass % or less, the stability of the actuator member is high. These cyanoethyl group-containing organic compounds are sold by Shin-Etsu Chemical Co., Ltd. under the product name Cyanoresin (registered trademark), for example.
[0036] (Other polar materials) The polar group-containing organic compound contained in the dielectric film of this embodiment may be modified silicone oil, phthalocyanines, various ionic liquids, or the like.
[0037] As the modified silicone oil, for example, a silicone oil that is liquid at room temperature (15 to 25° C.) and is obtained by modifying a compound having a polydimethylsiloxane skeleton with a polar group can be used.
[0038] Examples of polar groups that modify polydimethylsiloxane include -CH2CH2CF3 group (fluoroalkyl modified), O(EO)n- group (polyether modified), -OH group (hydroxyl modified), -NH2 group (amino modified), -CH2OH group (carbinol modified), -COOH group (carboxyl modified), etc. Modified silicone oils that have these polar groups may be side chain modified copolymer types or straight chain modified copolymer types, and the portion modified with the polar group may be any of the side chain, one end, or both ends.
[0039] Of these, preferred modified silicone oils are carboxyl-modified silicone oils with -COOH groups, fluoroalkyl-modified silicone oils with -CH2CH2CF3 groups, and amino-modified silicone oils with -NH2 groups.
[0040] For example, the carboxyl-modified silicone oil may be a random polymer or a block polymer. It is preferably a side chain type, and more preferably has a viscosity of 1000 to 8000 mm at 25°C. 2 The compound has a molecular weight of 100 / s and a functional group equivalent of 2000 to 6000 g / mol. The amount added is 5 to 60% by mass based on the total amount of the polymer actuator composition, but is preferably 10 to 40% by mass, and more preferably 20 to 30% by mass. If the amount added is less than 5% by mass, there is no effect of improving the displacement of the actuator, and if it exceeds 60% by mass, the acid value increases too much and the stability of the actuator member decreases. Commercially available carboxyl-modified silicone oils include X-22-3701E (side chain type, kinetic viscosity at 25°C: 2000 mm) manufactured by Shin-Etsu Chemical Co., Ltd. 2 / s, functional group equivalent: 4000g / mol) X-22-162C (double-ended type, 25℃ kinematic viscosity: 220mm 2 / s, functional group equivalent: 2300 g / mol).
[0041] Amino-modified silicones are silicone oils with a kinetic viscosity of 100 to 20,000 mm at 25°C. 2 / s is preferable, and 500 to 10,000 mm 2 / s. When the kinetic viscosity is in this range, the amino-modified silicone oil becomes easy to manufacture and handle. The kinetic viscosity can be measured by an Ostwald viscometer. The amino equivalent of the silicone oil is preferably 100 to 10,000 g / mol, and more preferably 1,200 to 4,000 g / mol. The amino equivalent can be determined by dividing the weight average molecular weight of the amino-modified silicone by the number of nitrogen atoms contained in the amino-modified silicone. The number of nitrogen atoms can be determined by elemental analysis.
[0042] A specific example of an amino-modified silicone oil available on the market is SS-3551 (dynamic viscosity 1000mm) from Dow Corning Toray Co., Ltd. 2 / s (25°C, amino equivalent 1600g / mol), FZ-3705 (kinetic viscosity 250mm 2 / s (25°C, amino equivalent 4000g / mol), FZ-319 (kinematic viscosity 2000mm2 / s (25°C, amino equivalent 4000g / mol), etc., and Shin-Etsu Chemical Co., Ltd.'s products: KF857, KF858, KF859, KF862, KF8001, KF880, and KF-864 (kinematic viscosity 1700mm 2 / s (25°C, amino equivalent 3800 g / mol).
[0043] As the ionic liquid, imidazolium salts, piperidinium salts, pyridinium compounds, pyrrolidinium salts, etc. can be used, but examples of the ionic liquid that can be used in the dielectric film of this embodiment include 1-methyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([EMI][TFSI]), 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMI][BF4]), 1-butyl-3-methylimidazolium tetrafluoroborate ([BMI][BF4]), 1-hexyl-3-methylimidazolium tetrafluoroborate ([HMI][BF4]), 1-ethyl-3-methylimidazolium 2-(2-methoxyethoxy)-ethylsulfate ([EMI][MEES]), 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide ([BMP][TFSI]), etc. It has also been reported that phthalocyanines, which are metal complexes having Mg, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Mo, Ru, Rh, Pd, Re, Os, Ir or Pt as the central metal, act as charge capture agents in the dielectric polymer layer and become charged inside the actuator (see JP 2005-323482 A).
[0044] <Internal structure and manufacturing method of dielectric film> In one embodiment shown in FIG. 1, the internal structure of the dielectric film has a sea-island structure consisting of a continuous phase (sea phase) made of a base polymer and a dispersed phase (island phase) mainly made of a polar group-containing organic compound. This configuration tends to make it easier for heterocharges to accumulate at the interface with the dense layer. The reason for this is thought to be as follows, although it is not particularly limited to the interpretation. When a polar group-containing organic compound with a large dielectric constant forms a dispersed phase of a certain size, the interfacial polarization due to the orientation of dipoles and impurities is maximized. Such a sea-island structure can be confirmed by using, for example, a laser microscope or an electron microscope such as a transmission electron microscope (TEM) or a field emission scanning electron microscope (FE-SEM).
[0045] The above-mentioned sea-island structure can be obtained by mixing the continuous phase constituent material and the dispersed phase constituent material in an appropriate ratio. Usually, the proportion A of the continuous phase constituent material is larger than the proportion B of the dispersed phase constituent material. For example, the ratio (A / B) of the proportion A of the continuous phase constituent material to the proportion B of the dispersed phase constituent material is suitably 1.1 or more, and preferably 1.2 or more.
[0046] In a preferred embodiment, the above-mentioned sea-island structure can be produced by mixing and stirring a solution of a polar group-containing organic compound (including a cyanoethyl group-containing organic compound and a modified silicone oil) dissolved in an appropriate solvent with a dissolved organopolysiloxane composition, applying the solution onto a PET film or the like, forming the desired shape, and curing the formed composition. The solvent is not particularly limited as long as it has an appropriate polarity and viscosity to disperse the polar group-containing organic compound in the organopolysiloxane composition and form the above-mentioned sea-island structure, and examples of the solvent include tetrahydrofuran (THF).
[0047] The molding method may be a method using a molding die, or for a thin film, a method of sandwiching the polymer actuator composition between release-treated films having spacers and passing through nip rolls with a controlled gap to a desired thickness. The curing conditions for the dielectric film are a temperature of 70 to 200°C, preferably 80 to 160°C, and 15 minutes to 24 hours. When the curing temperature of the dielectric film is 70°C or higher, the curability of the polymer actuator member is high, and when the curing temperature is 200°C or lower, the generation of by-products can be reduced. When the curing time of the dielectric film is 15 minutes or longer, the curability of the polymer actuator member is sufficient, and when the curing time is 24 hours or shorter, the deterioration of the polymer actuator member can be reduced.
[0048] The dielectric film thus obtained may be in the form of a thin film, film, or sheet, and has a thickness of 0.01 to 1.0 mm, preferably 0.05 to 0.5 mm. If the thickness of the member is 0.01 mm or more, dielectric breakdown due to defects in the film is unlikely to occur, while if it is 1.0 mm or less, the applied electric field strength becomes high, making it easier to drive the actuator.
[0049] <Polymer actuator member and polymer actuator using same> In the polymer actuator member according to another embodiment of the present invention, a polymer actuator can be fabricated by forming electrodes on both sides of the dielectric film. The material of the electrodes can be, for example, metals such as gold, platinum, aluminum, silver, copper, carbon, carbon nanotubes, or conductive resins or conductive elastomers in which these are dispersed in resin. The method of forming the electrodes can be, for example, plasma CVD, ion sputter coating, vacuum deposition, screen printing, or the like.
[0050] The polymer actuator of the present invention can be used not only as an actuator in industrial or nursing robots, medical equipment, and the like, but also as a sensor that detects a voltage change from its deformation.
[0051] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to these examples. In the following examples, the unit % of the numerical values showing the amount of each component added means % by mass. EXAMPLES
[0052] (Preparation of silicone composite material) 1.Material The silicone used as the base polymer was SILPOT184 / CAT184 (Toray DuPont Specialty Materials Co., Ltd.). This is an addition reaction type polydimethylsiloxane (PDMS) of polymethylhydrogensiloxane (PMHS). Cyanoethyl sucrose (CR-U, Shin-Etsu Chemical Co., Ltd.) with a cyanoethyl group (-CH2CH2CN) was used as the polar group-containing substance. CR-U was used as a 10-50% tetrahydrofuran (THF) or acetone (ACT) solution because of its high viscosity and easy handling. 10-50% solutions of CR-U were prepared using THF and ACT as solvents.
[0053] 2. Preparation of Mixture Solution A PDMS solution of SILPOT184 and CAT184 was adjusted to a mass ratio of 10:1, and the above CR-U 10-50% solution was mixed with this PDMS solution to make the CR-U concentration 20-42.9 mass%. To prepare the PDMS / CR-U mixed solution, mixing was performed by stirring at 2000 rpm for 2 minutes using a rotary stirrer (ARE-310, Thinky Co., Ltd.). The silicone composite film (dielectric film) for deformation measurement was made by casting the above-prepared mixed solution to a thickness of 150-280 μm on a 125 μm PET film placed on a glass plate using a four-sided film applicator (052-6, Allgood Co., Ltd.), leaving it for 30 minutes, and then heating it in an oven at 150 °C for 30 minutes to harden it. The CR-U composite material is denoted as PDMS / CR-U(y)x (x is the content (mass%) of the polar group-containing substance in the PDMS solution, and y represents the type of solvent in which it dissolves. PDMS / CR-U(T)x is used for THF solvent, and PDMS / CR-U(A)x is used for acetone solvent). The surface side of the PET substrate during film casting was designated as the "PET side", and the opposite air surface side was designated as the "air side". The prepared PDMS / CR-U mixed solution was poured into a Teflon Petri dish, and the Teflon Petri dish was vacuum degassed, after which the mixed solution for measuring the elastic modulus was heated in an oven at 150 °C for 60 minutes to harden. The silicone composite material was adjusted to a diameter of 30 mm and a thickness of 5 mm.
[0054] (Space charge distribution measurement) The spatial charge distribution was measured using a pulsed electrostatic acoustic nondestructive testing device (PEANUT) manufactured by Five Labs. Figure 2 shows an overview of the electrode part of the PEANUT device. The upper electrode 22 is made of semiconductive rubber, and the lower electrode 24 is made of aluminum. In the PEANUT method, a pulsed electrostatic force acts on the charge, generating an elastic wave with a charge distribution shape. This elastic wave was converted into an electrical signal by a piezoelectric element, and the spatial charge distribution was measured. The bias condition was 3 kV / mm, and the pulse condition was 200 V x 400 Hz.
[0055] (Bending deformation measurement) 1. Specimen Preparation: A schematic diagram of the deformation measurement sample is shown in Figure 3. The prepared silicone elastomer film 31 was cut to a width of 5 mm and a length of 20 mm, and gold foil 32 (Katani Sangyo Co., Ltd.) with a width of 4 mm, a length of 15 mm, and a thickness of 0.1 μm was attached to the front and back to prepare the deformation measurement sample.
[0056] 2.Deformation measurement: Figure 4 shows the experimental setup for measuring deformation. A DC power supply 44 was used with a square wave output of 850 V maximum output. To avoid the influence of its own weight, the test piece 43 was placed vertically to the floor, clamped with a Kelvin clip (12 mm from the clip to the tip of the test piece in a cantilevered state), and a DC voltage was applied. The deformation amount was observed and measured under an electric field with a digital microscope 41 placed on the sample, and recorded by a computer 42.
[0057] (Electrical characteristics) The dielectric constant and impedance were measured with an impedance analyzer (SI1260, SII1296, Solartron Co., Ltd.), a high voltage interface (HVI-100, TOYO Corporation), and a bipolar amplifier (BOP-1000M, KEPCO, INC.) (electrode diameter 10 mm and specimen thickness 170 μm).
[0058] (Compressive elastic modulus) The compressive modulus of the silicone composite material was measured using a Tensilon universal material testing machine (RTC-1250A, A&D Co., Ltd.) The silicone composite material was compressed with a 5 kN load cell at a rate of 0.5 mm / min.
[0059] (Structural composition) The structural composition was measured using FT / IR-4600 type A (JASCO Corporation) at an incident angle of 45 degrees.
[0060] (Photo taken) Cross-sectional images of the samples were taken with a laser microscope (OLYMPUS LEXT OLS4100).
[0061] result (Sample image) Figure 5 shows cross-sectional images of the composites PDMS / CR-U(T)17.9(a), PDMS / CR-U(T)24.7(b), PDMS / CR-U(T)30.4(c), and PDMS / CR-U(T)42.9(d) using tetrahydrofuran as a solvent, and PDMS / CR-U(A)17.9(e), PDMS / CR-U(A)24.7(f), PDMS / CR-U(A)30.4(g), and PDMS / CR-U(A)42.9(h) using acetone. Figure 6 shows enlarged images of PDMS / CR-U(T)42.9(a) and PDMS / CR-U42.9(A)(b). Figure 7 shows the dependence of the sphere diameter and dense layer thickness of each composite on the amount of addition. Each composite showed a sea-island two-phase structure. PDMS / CR-U(T)x showed an asymmetric cross-sectional structure in which the diameter of the spherical phase increased with increasing CR-U addition, and the air side had a dense layer that became thicker with increasing CR-U addition. Image analysis showed that PDMS / CR-U(T)42.9 had a structure with an average particle size of 28 μm and a dense layer of 13 μm. On the other hand, PDMS / CR-U(A)x had a symmetric cross-sectional structure without a dense layer in which small particles were uniformly dispersed, and PDMS / CR-U(A)42.9 had an average particle size of 2.7 μm.
[0062] (composition analysis) Figure 8 shows the ATR results comparing the air and PET surfaces, as well as the sea and island phases of PDMS / CR-U42.9(T). The absorption curves of the air and PET surfaces are almost identical to those of PDMS, but the siloxane bonds (Si-O-Si: 1100-1000, 500-450 cm -1 ) absorption was lower on the PET surface than on the air surface. A clear absorption of CR-U (-CN group: 2,253 cm) was observed on the air surface. -1 ) was not observed, and strong absorption was confirmed on the PET surface. In addition, the absorption curves of the sea phase and island phase were almost identical to that of PDMS, but the absorption of siloxane bonds was slightly weaker in the island phase than in the sea phase. On the other hand, no clear absorption of -CN groups was observed in the sea phase, and strong absorption was confirmed in the island phase. From these results, it was revealed that the PET surface and island phase are considered to be a mixture of PDMS components and dense CR-U components, and that the air surface and sea phase are PDMS components.
[0063] (Solution compatibility) To confirm the compatibility of each material, we prepared a 50% solution of CR-U in THF (CR-U(T)50), a 50% solution of ACT (CR-U(A)50), a 21% solution of PDMS in THF (PDMS(T)21), a 21% solution of ACT (PDMS(A)21), and three-component solutions of PDMS / CR-U(T)42.9 and PDMS / CR-U(A)42.9. Figure 9 shows the appearance change after mixing the solutions, placing them in a test tube, and leaving them for 120 minutes. CR-U(T)50 and CR-U(A)50 maintained their transparency even after 120 minutes had passed since mixing. PDMS(T)21 remained transparent even after 120 minutes had passed since mixing, but PDMS(A)21 separated into two phases after 30 minutes. Immediately after mixing, PDMS / CR-U(T)42.9 showed a low-viscosity, cloudy solution, and after 30 minutes, the solution separated into a transparent upper layer and a milky lower layer consisting of aggregates of small particles. After 120 minutes, aggregates of relatively large, transparent, spherical phases were observed in the lower layer. The lower layer was sticky. From this, it is believed that the upper layer is a PDMS layer and the lower layer is a CR-U layer. On the other hand, PDMS / CR-U(A)42.9 showed a milky white color immediately after mixing, and showed a high viscosity with a thixotropic property, and the state inside the test tube did not change.
[0064] This is because THF has a high affinity for PDMS and CR-U, and the viscosity of the solution is relatively low, so it is believed that small particles of CR-U gradually aggregate during the drying and standing process, causing the large spherical phase to grow and settle. This is also consistent with the fact that the specific gravity of the materials is 1.08 for PDMS and 1.23 for CR-U. This change in state is believed to have resulted in a cross-sectional structure with a dense layer on the air side and a non-dense layer on the PET side. On the other hand, when ACT, which has a low affinity for PDMS, was used, it is believed that PDMS became entangled with CR-U, resulting in high viscosity. As a result, it is believed that the aggregation of the CR-U phase was suppressed, resulting in a cross-sectional structure with small particles dispersed.
[0065] (Electrical characteristics) 1.CR-U addition amount dependence Figure 10 shows the CR-U content dependence of the AC impedance of PDMS, PDMS / CR-U(T)x, and PDMS / CR-U(A)42.9 at a bias of 3 kV / mm. Only the Cole-Cole plot of PDMS / CR-U(T)42.9 drew a circular arc, and an equivalent circuit was obtained from the equivalent circuit analysis in which a parallel circuit of a resistor and a capacitor was connected in series with an equivalent circuit. The other composites showed the characteristics of an insulating material, with the imaginary number Z" rising sharply. Figure 11 shows the relationship between the resistance and capacitance obtained from the equivalent circuit analysis and the CR-U content. The capacitance increased with increasing CR-U content, and the resistance dropped sharply when the CR-U content was 35.3 wt% or more. No polarization was observed in PDMS / CR-U(A)42.9, but only in PDMS / CR-U(T)42.9.
[0066] 2. Bias Dependence Figure 12 shows the electric field strength dependence of the AC impedance of PDMS / CR-U(T)42.9. As the electric field strength increases, the arcs of the Cole-Cole plot become clearer, and an equivalent circuit is obtained in which a capacitor is in series with a parallel circuit of a resistor and capacitor. Figure 13 shows the results of the electric field strength dependence of the resistance and capacitance obtained from the equivalent analysis. As the electric field strength increases, the capacitance increases and the resistance gradually decreases. From these results, polarization progresses with increasing electric field strength, and clear polarization is observed at electric field strengths of 2.35 kV / mm and above.
[0067] (Displacement measurement) 1.CR-U addition amount dependence Figure 14 shows the dependence of the displacement after 30 minutes at an electric field strength of 3 kV / mm for PDMS / CR-U(T)x and PDMS / CR-U(A)x on the amount of CR-U added when the electric field direction was changed. The displacement of PDMS / CR-U(T)x gradually increased with increasing amount of added CR-U, and from an amount of added 24.7 mass% or more, it showed displacement toward the PET side regardless of the electric field direction, and increased rapidly from about 35.3 mass%. No dependence on the amount of added PDMS / CR-U(A)x was observed, and it showed a very small displacement in the negative direction regardless of the electric field direction.
[0068] 2. Electric field strength dependence Figure 15 shows the electric field strength dependence of the displacement of PDMS / CR-U(T)42.9 and PDMS / CR-U(A)42.9. An electric field was applied for 1 minute at each strength, and measurements were taken while changing the electric field direction. PDMS / CR-U(T)42.9 showed displacement in the direction of the PET surface, regardless of the magnitude of the applied voltage or the electric field direction. On the other hand, PDMS / CR-U(A)42.9 showed a small amount of displacement in the direction of the cathode, regardless of the electric field direction.
[0069] 3. Behavior of dense layer under voltage To confirm the behavior of the dense layer under voltage load, a 12 μm PE film was attached (laminated) to the Au foil on the air side and the PET side of the PDMS / CR-U(T)42.9, and the displacement was measured for 30 minutes at an electric field strength of 3 kV / mm. The results are shown in Figure 16. It was confirmed that there was almost no displacement when the PE film was laminated on the air side. This is the result of forcibly suppressing the elongation of the dense layer, and it is believed that the elongation of the dense layer was involved in the displacement behavior.
[0070] (Space charge distribution measurement) Since elastic waves are greatly attenuated inside the elastomer film, the space charge distribution was measured using the measurement and evaluation method described in T. Murakami et al., IEE Japan., 11-A(6), 647-648 (1997). The space charge distribution at the upper electrode interface away from the piezoelectric element is inaccurate, so measurements were taken by changing the polarity of the bias voltage, focusing on the space charge distribution at the electrode interface on the piezoelectric element side (lower aluminum electrode side). Measurements were taken on both the front and back of the sample. The graph shows the measurement results near the lower electrode interface of positive and negative polarity on the same graph. The maximum value of the positive or negative charge accumulated inside the film was taken as the different charge peak value.
[0071] 1.Additional amount dependence The results of space charge measurements for PDMS / CR-U(T)42.9 and PDMS / CR-U(A)42.9 are shown in Figure 17. The horizontal axis of the graph indicates the sample thickness (position) when the anode and cathode sample interfaces are set to zero, and the vertical axis indicates the space charge density. For PDMS / CR-U(T)42.9, an accumulation peak of charge opposite to the polarity of the electrode was observed around 10 to 30 μm inside the sample (deep) near the air side electrode sample interface, regardless of the electric field direction. The position of this peak coincided with the vicinity of the dense layer. This is thought to be because the dense layer suppresses charge leakage, and charge accumulates near the dense layer.
[0072] The homogeneous charge accumulation near the electrode sample interface on the PET side, which does not have a dense layer, was smaller than that on the air side, and slight heterogeneous charge accumulation was observed inside the sample, but asymmetry of the space charge distribution was confirmed. On the other hand, PDMS / CR-U(A)42.9 showed a symmetrical space charge distribution with no charge accumulation inside the sample regardless of the electric field direction.
[0073] Figure 18 shows the dependence of space charge distribution on the amount of CR-U added for each composite when the bias polarity was changed. For composites using THF, accumulation of heterogeneous charges was observed inside the sample near the air-side electrode-sample interface for composites with 35 wt% or more CR-U, regardless of the electric field direction, and the amount of accumulation increased with increasing additive amount. Only PDMS / CR-U(T)42.9 showed asymmetry of space charge, with slight accumulation of heterogeneous charges observed inside the sample near the PET-side electrode-sample interface, regardless of the electric field direction.
[0074] 2. Displacement and heterocharge peak value The relationship between the hetero charge peak value and the displacement of PDMS / CR-U(T)x is shown in Figure 19. It was confirmed that the displacement increased with an increase in the hetero charge peak value, regardless of the electric field direction.
[0075] (Phase separation structure and polarization) A large difference was observed in the displacement behavior between the fine dispersion system PDMS / CR-U(A)42.9 with small sphere diameter and the large particle dispersion system PDMS / CR-U(T)42.9. In a study of the dielectric breakdown of a composite of polymer materials and inorganic fillers, it is known that the presence of filler particles with different dielectric constants in the base material of a fine particle composite material, compared to a homogeneous material, generates a polarization charge, distorts the electric field lines and equipotential surfaces, makes the intervals equal, and the potential gradient is not constant. In addition, it is known that the treeing breakdown time for the dielectric breakdown characteristics increases as the nanofiller diameter decreases. The results of the examples so far are summarized in Table 1. The results of dielectric relaxation, surface resistivity, etc. suggest that the dispersion system of silicone cyanoethyl saccharose composites also show similar results to those of polymer materials and inorganic filler composites.
[0076] [Table 1]
[0077] In other words, the specific displacement behavior of the silicone cyanoethyl saccharose composite is considered to be due to the fact that the influence of the electric field on each particle is significant in the small particle dispersion system, resulting in a small interfacial polarization and a small macroscopic dielectric relaxation strength. On the other hand, the large particle diameter PDMS / CR-U(T)42.9 has a three-dimensional network dispersion structure of the dielectric phase, which causes interfacial polarization. In addition, the asymmetric cross-sectional structure with the dense layer is considered to have induced the specific displacement due to the charge accumulation and the asymmetry of the elastomer properties on the front and back. Figure 20 shows a schematic diagram of the space charge distribution and deformation near the anode interface when the dense layer side is the anode. It is considered that the displacement of silicone / cyanoethyl saccharose using THF was due to the electrostatic repulsion of the charge accumulated near the interface between the spherical phase of CR-U and the dense layer, which caused the dense layer to elongate, resulting in a displacement in the direction of the non-dense layer.
[0078] Finally, the dependence of the compressive modulus of PDMS / CR-U(T)x, which is a basic physical property of elastomers, on the amount of CR-U added is shown in Figure 21. There was no dependence on the amount of CR-U added, and PDMS / CR-U(T)42.9 maintained 1 MPa, confirming that there are no practical problems. [Explanation of symbols]
[0079] 10 Dielectric film 11 Anode / component interface 12 Sea-island structure 13 Base polymer (continuous phase) 14 Dispersed phase 15 Interface 21 Al electrode 22 Upper electrode (semi-conductive rubber) 23, 31, 43 Silicone elastomer film (dielectric film) 24 Lower electrode (Al) 25 Piezo element (sensor) 32 Gold leaf 41 Digital Microscope 42 Computer 44 DC power supply
Claims
1. A dielectric film containing a dispersed phase of a polar group-containing organic compound in a base polymer, the dielectric film having a dense layer made of the base polymer on one surface of the dielectric film.
2. 2. The dielectric film of claim 1, wherein the base polymer comprises one or more elastomers selected from silicone, polyurethane, polyacrylonitrile, nylon, polyethylene terephthalate, polypropylene, polyethylene, polyketone, polyvinyl alcohol, polyvinyl butyral, polyvinyl acetate, polymethyl methacrylate, poly-n-butyl acrylate, cellulose, and wool.
3. 3. The dielectric film according to claim 1, wherein the polar group-containing organic compound is a cyanoethyl group-containing organic compound, a modified silicone oil, a phthalocyanine, or an ionic liquid.
4. 4. The dielectric film according to claim 3, wherein the cyanoethyl group-containing organic compound is at least one selected from the group consisting of cyanoethyl sucrose, cyanoethyl pullulan, cyanoethyl cellulose, cyanoethyl hydroxyethyl cellulose, cyanoethyl hydroxypropyl cellulose, cyanoethyl amylose, cyanoethyl starch, cyanoethyl dihydroxypropyl starch, cyanoethyl glycidol pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl polyhydroxymethylene, and cyanoethyl sorbitol.
5. 4. The dielectric film according to claim 3, wherein the modified silicone oil is a modified silicone oil having a polysiloxane chain and a fluoroalkyl group, a carboxyl group and / or an amino group bonded to an end or a side chain of the polysiloxane chain.
6. 6. The dielectric film according to claim 1, having a thickness of 50 to 500 μm and an asymmetric cross-sectional structure.
7. 7. The dielectric film according to claim 1, wherein the dispersed phase is spherical and has a diameter of 1 to 100 μm.
8. 8. The dielectric film according to claim 1, wherein the thickness of the dense layer is less than 10% of the total thickness of the dielectric film.
9. 9. The dielectric film according to claim 1, wherein the dense layer has a thickness of 5 to 50 μm.
10. A polymer actuator member comprising the dielectric film according to any one of claims 1 to 9 and an electrode layer on each of both sides of the dielectric film.
11. An actuator comprising the polymer actuator member according to claim 10.
Citation Information
Patent Citations
Dielectric material and transducer using the same
JP2011201993A
Enhanced surfaces, coatings, and related methods
JP2012500865A
Three-dimensional structure and method for production thereof
WO2004113056A1
Reactive ionic liquid, ion-fixing metal oxide particles using same, ion-fixing elastomer, and transducer
WO2013146357A1
